Pharmacobiology of topical Ankaferd hemostat in neoplastic disorders - Malkan, Ümit Yavuz; Haznedaroğlu, İbrahim Celalettin (The European Research Journal, 2023)
Ankaferd Hemostat (ABS) is a hemostatic agent of plant-extract acting on red blood cells used for achieving hemostasis. ABS has anti-inflammatory, anti-microbial, anti-fungal, anti-oxidative and anti-neoplastic effects. Cancer treatment is a challenging clinical condition that can lead to numerous clinical complications of different severity. Antineoplastic features of ABS had been depicted in many solid and hematological tumors. Supportive treatment of cancer is very important to decrease the mortality and morbidity of the cancer patients. ABS prevents and treats chemotherapy associated mucositis with its unique effects on the blood cells, endothelium, angiogenesis, cellular regeneration, wound healing and vascular dynamics. Those features of ABS bring it to be also beneficial for necrotizing enterocolitis as well. Besides its supportive and preventative roles in the cancer patients, ABS can also be potentially utilized as a chemoembolization agent within intratumoral treatment modality. The aim of this review is to summarize current pharmacobiology of topical ABS in neoplastic disorders.